Evaluating a Newly Developed Differentiation Approach in Terms of Student Achievement and Teachers' Opinions - (:unkn) unknown (My University, 2015)
0

This study aims to evaluate a differentiation approach that was recently developed to teach mathematics to gifted middle school students in terms of its practice by teachers by studying the effect of the approach on achievement among both gifted and non-gifted students. From mixed research methods, the study used an explanatory design. It was conducted with 68 gifted and 144 non-gifted students who were in the 5th, 6th and 7th grades and 5 mathematics teachers. A mathematics achievement test, the Multiple Intelligences Inventory, and a teachers' opinion form were used as the data collection instruments. When the lessons that were designed according to the recently developed differentiation approach were compared with the lessons that were conducted according to the Ministry of National Education curriculum, those lessons designed according to the Purdue model, and those that were conducted within the scope of differentiation that was outlined in the Program for Noticing Individual Skills, the participating students' achievements increased significantly with the use of the recently developed differentiation approach. In addition, the teachers expressed that the activities that were conducted based on the differentiation approach were creative, beneficial, and tailored to the students' levels, and they addressed different intelligences types. The teachers reported that the students were more active; the lessons were more effective; the students improved their academic and social skills; and they had opportunities to understand their students better; understand the importance of project studies; and experience the project management process
Keywords: Eğitim, Eğitim Araştırmaları